The Role of Self-Blaming Moral Emotions in Major Depression and Their Impact on Social-Economical Decision Making - Pulcu, Erdem; Zahn, Roland; Elliott, Rebecca (Frontiers in Psychology, 2013)
People with major depressive disorder (MDD) are more prone to experiencing moral emotions related to self-blame, such as guilt and shame. DSM-IV-TR recognises excessive or inappropriate guilt as one of the core symptoms of current MDD, whereas excessive shame is not part of the criteria for MDD. However, previous studies specifically assessing shame suggested its involvement in MDD. In the first part of this review, we will consider literature discussing the role of self-blaming moral emotions in MDD. These self-blaming moral emotions have been purported to influence people when they make social and financial decisions in cognitive studies, particularly those using neuroeconomical paradigms. Such paradigms aim to predict social behaviour in activities of daily living, by using important resource tangibles (especially money) in laboratory conditions. Previous literature suggests that guilt promotes altruistic behaviour via acting out reparative tendencies, whereas shame reduces altruism by means of increasing social and interpersonal distance. In the second part of this review, we will discuss the potential influence of self-blaming moral emotions on overt behaviour in MDD, reviewing clinical and experimental studies in social and financial decision-making, in which guilt and shame were manipulated. This is not a well-established area in the depression literature, however in this opinion paper we will argue that studies of moral emotions and their impact on behavioural decision-making are of potential importance in the clinical field, by linking specific symptoms of a disorder to a behavioural outcome which may lead to stratification of clinical diagnoses in the future.